Latin America and the Caribbean and China : towards a new era in economic cooperation (UN ECLAC SantiagoCL, 2015)
Analyses the main features of the internaitonal economic context for Latin America and the Caribbean and China. Examines progress. Offers and overview of the region's treade and investment relations with China. Discusses some of the main components of the China CELAC Cooperation Plan 2015-2019 which was adopted by the Community of Latin American and Caribbean States anc China (CELAC) in January 2015.
Keywords: CHINA